Occupational stress and associated factors among nurses working at public hospitals of Addis Ababa, Ethiopia, 2022; A hospital based cross-sectional study - Werke, Elshaday Bekele; Weret, Zewdu Shewangizaw (Frontiers in Public Health, 2023)
Background By its very nature, the nursing profession involves a lot of stress. Working in this field includes interacting with individuals who are already under a great deal of stress. Workplace stress affects the quality of services provided and also causes staff burnout, departure, and absenteeism. Objective This study is to determine occupational stress and associated factors among nurses working at public hospitals, Addis Ababa, Ethiopia, 2022. Materials and methods An institutional based cross sectional study was conducted among 422 nurses working at public hospitals from March 1 to April 1/2022. Simple random sampling technique was used to select public hospitals. The calculated sample size was allocated proportionally to each hospital based on the number of nurses. Finally, systematic sampling method was used to approach the study participants. The data was collected by using a self-administered structured questionnaire (Expanded Nursing Stress Scale). The collected data was entered by Epi-data version 3.1 and analyzed by SPSS version 23. Descriptive analysis such as frequency distribution and measure of central tendency and variability (mean and standard deviation) was computed to describe variables of the study. Binary logistic regression was used to assess associations between dependent and independent variables. The degree of associations was interpreted using odds ratio (OR) and 95% confidence interval (CI) and statically significance at value of p < 0.05. The result was presented using text, tables, and graphs. Result The study finding showed that 198 (47.8%) of nurses were occupationally stressful. Factors significantly associated with occupational stress among nurses were having children (no: AOR = 0.46, 95% CI: 0.22, 0.96) and work shift (rotating: AOR = 2.89, 95% CI: 1.87, 4.45). Conclusion In this study, job stress affected over half of the nurses. The presence of children and respondents’ work shifts were personal characteristics that were significantly linked to job stress. Therefore based on this result the government policy makers, different stakeholders and hospitals need to collaborate to reduce nurses job related stress.